Commodification of Betawi culture of Palang Pintu festival - Suraya Mansur; Nurhayani Saragih; Wiwik Novianti; S Bekti Istiyanto; Utas Mahligai (Informasi, 2022)
The Kemang Palang Pintu Festival is an annual event. The purpose of this event is to preserve culture and celebrate the anniversary of the city of Jakarta. The organizers display many Betawi cultural arts while visitors who come are not only Betawi residents. This study uses a constructivist qualitative approach. The research method used is a case study by conducting interviews direct observation to make observations. The technique of checking the validity of the data is using the source triangulation technique. The results of this study indicate that the Kemang Palang Pintu Festival has carried out good planning. Starting from selection of participants, the technical meeting of event agenda, to the mechanism of the event rundown. Have conducted a visitor satisfaction survey but have not processed the data as a reference for the next implementation. The technique of compiling messages has been well designed in order to attract visitors and convey the meaning of the message that is the purpose of the event. This doorstop festival is a commodity process that provides selling power. The advantages in this case are various forms, both material and non-material (the existence of sanggar studios).